2005
DOI: 10.1248/cpb.53.508
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of the Marker Compounds in Salvia miltiorrihiza Root and Its Phytomedicinal Preparations

Abstract: A HPLC method is described in order to separate and identify 4 phenolic compounds including lithospermic acid B, 3,4-dihydroxyphenyllactic acid (danshensu), rosmarinic acid, and protocatechuic aldehyde as well as 3 lipophilic ones (tanshinone I, tanshinone II A and cryptotanshinone) from the roots of Salvia miltiorrihiza or the herbal product containing S. miltiorrihiza available in Chinese or Japanese market. The influence of extractive conditions, such as method, solvents and time, on the 4 phenolic marker c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 25 publications
(15 reference statements)
1
23
0
Order By: Relevance
“…The CM is a serumfree medium with 24 h incubation with phorbol myristate acetate-treated THP-1 cells. Our previous studies and the other reports showed that the CM might contain proinflammatory cytokines such as tumor necrosis factor-a, IL-1, IL-8, and IL-12; anti-inflammatory cytokines such as transforming growth factor-h, IL-4, IL-10, and IL-13; and IL-6 with both proinflammatory and anti-inflammatory properties (3,11,27,39,40). Previous reports have shown that the imbalance between proinflammatory and anti-inflammatory cytokines can influence neoplastic outcome (3).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The CM is a serumfree medium with 24 h incubation with phorbol myristate acetate-treated THP-1 cells. Our previous studies and the other reports showed that the CM might contain proinflammatory cytokines such as tumor necrosis factor-a, IL-1, IL-8, and IL-12; anti-inflammatory cytokines such as transforming growth factor-h, IL-4, IL-10, and IL-13; and IL-6 with both proinflammatory and anti-inflammatory properties (3,11,27,39,40). Previous reports have shown that the imbalance between proinflammatory and anti-inflammatory cytokines can influence neoplastic outcome (3).…”
Section: Discussionmentioning
confidence: 96%
“…The structures of tanshinones and their yield properties in root of S. miltiorrhiza Bunge are shown in Fig. 1 (27). Dexamethasone was purchased from the Sigma.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, this technique has been accepted by WHO as a methodology for the assessment of TCM, and is also taken as a method for quality control of TCM in Chinese Pharmacopoeia [3]. Moreover, it is widely accepted that multiple constituents are responsible for the therapeutic effects of TCM; therefore, to ensure its quality, it is necessary to quantitatively determine the multiple marker compounds simultaneously [4].…”
Section: Introductionmentioning
confidence: 99%
“…Analytical methods for the quantitative determination of the active tanshinones, tanshinone I, dihydrotanshinone I, tanshinone IIA and cryptotanshinone, in Salvia miltiorrhiza plants and medicinal preparations have been reported (Hu et al, 2005;Shi et al, 2005;Yuan et al, 2005;Liu et al, 2006;Yang et al, 2006;Zhou et al, 2006;Ma et al, 2007). Cryptotanshinone was metabolized to a major metabolite, tanshinone IIA, and trace amounts of several hydroxyl-and dihydroxyl-cryptotanshinone in rats (Li et al, 2005;Song et al, 2005;Hao et al, 2006a;Sun et al, 2007a,b).…”
Section: Introductionmentioning
confidence: 99%